Pengaruh Digital Marketing, Kualitas Produk dan Harga Terhadap Minat Beli Pelanggan Pada Coffeshop di Kota Banjarbaru - Yudi; Rifqi Amrulloh; Fredy Jayen; Tina Lestari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to ascertain how customers' interest in purchasing from coffee shops in Banjarbaru City is affected by digital marketing, product quality, and price. This study's population consists of all customers of Loka Coffe & Eatery, Terjibakkopi, and Kean Coffe, three coffee shops in the city of Banjarbaru that receive over 500 visitors per month. Purposive sampling was used to select 120 respondents for this study's sample. In this study, multiple linear regression analysis was used. Blended research information utilizing Microsoft Succeed and SPSS 28 programming. The autonomous factors in this study are Advanced Showcasing (X1), Item Quality (X2), and Value (X3). The variable that is bound in this study is Client Purchasing Interest (Y). Digital marketing, product quality, and price all have a simultaneous effect on customer buying interest, according to this study's findings. Computerized Showcasing factors, Item Quality and Cost likewise impact Client Purchasing Interest. The bound variable, Customer Buying Interest, was 61.1% influenced by the independent variables (Digital Marketing, Product Quality, and Price). Additionally, Customer Buying Interest is primarily influenced by the Digital Marketing variable.The purpose of this study is to ascertain how customers' interest in purchasing from coffee shops in Banjarbaru City is affected by digital marketing, product quality, and price. This study's population consists of all customers of Loka Coffe & Eatery, Terjibakkopi, and Kean Coffe, three coffee shops in the city of Banjarbaru that receive over 500 visitors per month. Purposive sampling was used to select 120 respondents for this study's sample. In this study, multiple linear regression analysis was used. Blended research information utilizing Microsoft Succeed and SPSS 28 programming. The autonomous factors in this study are Advanced Showcasing (X1), Item Quality (X2), and Value (X3). The variable that is bound in this study is Client Purchasing Interest (Y). Digital marketing, product quality, and price all have a simultaneous effect on customer buying interest, according to this study's findings. Computerized Showcasing factors, Item Quality and Cost likewise impact Client Purchasing Interest. The bound variable, Customer Buying Interest, was 61.1% influenced by the independent variables (Digital Marketing, Product Quality, and Price). Additionally, Customer Buying Interest is primarily influenced by the Digital Marketing variable.